An Intrathermocline Eddy Observed in the Northeastern Bay of Bengal. Issue 12 (15th June 2022) - Zhou, Xiwu; Qiu, Yun; Lin, Xinyu; Teng, Hui; Aung, Cherry
Abstract: An intrathermocline eddy (ITE) was detected to the northwest of Preparis Channel by in situ measurements in January 2018. The ITE had a horizontal extent of approximately 200 km and a maximum velocity of approximately 60 cm/s at core depths between 75 and 130 m. This ITE was generated by the transformation from a preexisting surface‐intensified anticyclonic eddy (SAE). The blocking of the northeast monsoon by the Arakan Yoma Mountains resulted in a weak wind stress on the leeward side of the mountains. This caused positive Ekman pumping around Preparis Channel together with eddy wind‐driven upwelling, shoaling the upper thermocline in the SAE, and thus turning it into an ITE. Among the 71 anticyclonic eddies detected by Argo profiles around Preparis Channel from 2003 to 2018, approximately 60% were ITEs, indicating that Preparis Channel could be the main source for ITE generation in Bay of Bengal. Plain Language Summary: The interior of the ocean is populated by intrathermocline eddys (ITEs), and numerous ITEs play a vital role in the transport and redistribution of heat and salt in the global ocean. Although ITEs have been observed in many regions, little is known about the behavior and dynamics of ITEs in the Bay of Bengal (BOB). Recent studies (Gordon et al., 2017, https://doi.org/10.1038/srep46218 ; Jithin & Francis, 2021, https://doi.org/10.1029/2021jc017725 ) have found several ITEs in the central and northern BOB and have speculated that they originated from the Andaman Sea. Based on new in situ observations, we report an ITE around the eastern boundary of the bay. The ITE was generated from the transformation of a preexisting surface anticyclonic eddy caused by the disturbed winds on the leeward side of the Arakan Yoma Mountains and eddy wind‐driven upwelling. Our study presents the first clear observational evidence of wind‐induced transformation of surface eddies into ITEs as proposed by McGillicuddy (2015, https://doi.org/10.1175/jpo-d-14-0221.1 ). In addition, this study also shows that Preparis Channel could be the main source for ITE generation in the BOB, which potentially plays an important role in water mass exchange between the BOB and Andaman Sea. Key Points: Sampling of an intrathermocline eddy (ITE) leeward of the Arakan Yoma Mountains of Myanmar The first clear evidence of wind‐induced transformation of surface eddies into ITEs Preparis Channel could be the main source for ITE generation in the Bay of Bengal